Continuous quality improvement strategy for increasing immediate postpartum long-acting reversible contraceptive use at Jimma University Medical Center, Jimma, Ethiopia - Gurmesa Tura Debelew; Demisew Amenu Sori; Lema Seboka Degefa; Zerihun Asefa (BMJ Open Quality)
Background Even though the immediate postpartum period is a golden time and a great opportunity to provide long-acting reversible contraceptives to prevent unintended pregnancy, its utilisation is very low in Ethiopia. Quality of care in postpartum long-acting reversible contraceptive provision is thought to be an issue for this low utilisation. Thus, continuous quality improvement intervention is necessary to increase the use of postpartum long-acting reversible contraceptives at Jimma University Medical Center.Method A quality improvement intervention to offer long-acting reversible contraceptive methods to immediate postpartum women at Jimma University Medical Center was initiated in June 2019. To study the baseline prevalence of long-acting reversible contraceptive use at Jimma Medical Centre over 8 weeks, we reviewed postpartum family planning registration logbooks and patients’ charts. Based on the baseline data, the quality gaps were identified, prioritised and change ideas were generated and tested over another 8 weeks towards achieving the immediate postpartum long-acting reversible contraceptive prevalence target set.Result This new intervention resulted in an average increase in immediate postpartum long-acting reversible contraceptive methods use from 6.9% to 25.4% by the end of the project intervention. The major barriers to low long-acting reversible contraceptive use were lack of attention from hospital administrative staff and quality improvement teams on the provision of long-acting reversible contraceptives, lack of training of healthcare providers on postpartum contraception and unavailability of contraception commodities at each postpartum service delivery points.Conclusion and recommendations The immediate postpartum long-acting reversible contraceptive use at Jimma Medical Centre was increased by training of healthcare providers, availing contraception commodities through administrative staff involvement, weekly audit and feedback on contraception use. Thus, training of the newly hired healthcare providers on postpartum contraception, involvement of hospital administrative staff, regular audits and feedback on contraception use is necessary to increase postpartum long-acting reversible contraception uptake.